Tendência da distribuição das internações por condições sensíveis à atenção primária relacionadas às doenças crônicas não transmissíveis no Estado de São Paulo no período de 2016 a 2022 - Pereira, Helena Nayara Santos (Universidade Federal de São Carlos, 2024)
To analyze the trend of hospitalizations for ambulatory care sensitive conditions (ACSC) related to non-communicable chronic diseases (NCDs) from 2016 to 2022 in the state of São Paulo. Method: This is an ecological study using secondary data from ICSAP related to NCDs in the State of São Paulo, obtained from the Hospital Information System (SIH) of DATASUS. The independent variables included sex, age, cause of admission, nature of admission, and ZIP code of the municipality of residence. Descriptive analyses were conducted for the independent variables, as well as for incidence, mortality, and lethality (dependent variables). To evaluate the spatial autocorrelations of the variables of interest, univariate and bivariate Global Moran's Indices were calculated; after estimating the global indices, bivariate Local Moran's indices were calculated, allowing the identification of clusters. Changes in monthly rates between 2020 and 2023 were analyzed using a joinpoint regression model based on Poisson regression. Results: ICSAP accounted for an average of 7.6% of total admissions during the study period, with 2016 recording the highest number of ICSAP among general admissions, representing 8.24% of the admissions that year. It was found that the majority of NCD admissions were recorded among males in all analyzed years, with an average of 52.8%, and the highest number of admissions was recorded in the age group 60 to 69 years, followed by the age group 70 to 79 years. An increase in the number of deaths was observed between 2019 and 2021, with 2020 and 2021 showing the highest numbers during the period, followed by a reduction in 2022. The leading cause of hospitalizations was cerebrovascular diseases, followed by diabetes mellitus (DM), with a reduction in hospitalizations related to hypertension (HAS) and stable cases of angina between 2019 and 2022. Pulmonary diseases and asthma showed variations over the years, with increases between 2020 and 2022. Regarding heart failure, a significant increase was recorded in 2022. In the State of São Paulo, two periods of reduction in global ICSAP averages related to NCDs were observed, from August 2017 to February 2018 and from June 2020 to December 2022. A slight positive spatial correlation was also noted between the ICSAP coefficient and GDP in 2022, indicating that municipalities with higher coefficients tended to have higher GDPs. Additionally, a slight positive spatial correlation was observed between the ICSAP coefficient and GDP per capita in 2016, 2021, and 2022, suggesting that municipalities with higher ICSAP coefficients also tended to have higher GDP per capita. In the univariate analysis, a slight positive spatial correlation was found between the ICSAP coefficient related to NCDs in all analyzed years. This means that the values of the Global Moran Index (GMI) indicated a direct, albeit slight, correlation, as they were positive and close to zero, indicating statistical significance in all years. Conclusion: It is concluded that there is a slight positive spatial correlation between the ICSAP coefficient and GDP in 2022, indicating that municipalities with higher ICSAP coefficients had higher GDPs. A positive correlation was also observed between the ICSAP coefficient and GDP per capita in 2016, 2021, and 2022. Most RAs showed changes in admission trends during the COVID-19 pandemic, with an initial increase in NCD admissions followed by a subsequent decrease. This pattern was more evident in the RAs of Barretos, Sorocaba, São José dos Campos, São José do Rio Preto, Santos, Ribeirão Preto, and Itapeva, suggesting that the pandemic may have exacerbated NCDs.
Trend in the distribution of hospitalizations due to primary care-sensitive conditions related to chronic non-communicable diseases in the State of São Paulo from 2016 to 2022
Keywords: Doenças não transmissíveis; Condições Sensíveis à atenção primária; Atenção primária à saúde; CIENCIAS DA SAUDE::ENFERMAGEM